2012
DOI: 10.1074/jbc.m111.281709
|View full text |Cite
|
Sign up to set email alerts
|

Macro Histone H2A1.2 (MacroH2A1) Protein Suppresses Mitotic Kinase VRK1 during Interphase

Abstract: Background: VRK1 phosphorylates mitotic histone H3 at Thr-3 and Ser-10, but its negative regulator was not elucidated during interphase. Results: The macrodomain of macroH2A1 interacts with VRK1, and this suppresses enzymatic activity of VRK1 during interphase. Conclusion: Specific binding between VRK1 and macroH2A1 is required to regulate the cell cycle-dependent histone H3 phosphorylation. Significance: Understanding epigenetic regulation of histone H3 during the cell cycle is important in cancer development. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 30 publications
0
65
0
2
Order By: Relevance
“…VRK1 kinase activity is regulated by the folding of its C-terminal region [29,49] that results in a conformational change in native protein that is recognized by a specific monoclonal antibody (1B5) [45]. Previous work has shown this structural change in cells upon DNA damage response to ionizing radiation [31].…”
Section: The Basal Vrk1-p53 Complex Is Immediately Activated In Respomentioning
confidence: 99%
See 3 more Smart Citations
“…VRK1 kinase activity is regulated by the folding of its C-terminal region [29,49] that results in a conformational change in native protein that is recognized by a specific monoclonal antibody (1B5) [45]. Previous work has shown this structural change in cells upon DNA damage response to ionizing radiation [31].…”
Section: The Basal Vrk1-p53 Complex Is Immediately Activated In Respomentioning
confidence: 99%
“…The VRK1 C-terminal region (residues 275-396) is characterized by its low complexity [49] and its flexibility [49]. This C-terminal region has been described to interact with several proteins and to play a regulatory role [28,29,31]. For these reasons, next we analysed if this VRK1 region was binding to p53 by performing pull-down assays and with two different GST-VRK1 constructs [44]; full-length VRK1 (residues 1-396) and VRK1DN comprising the C-terminus (residues 267-396) (Fig.…”
Section: Vrk1 Stably Interacts With P53 Forming a Basal Protein Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…This phosphorylation was confirmed in vitro and in HEK293 cells, where overexpression of Haspin caused hyper-phosphorylation of Histone macroH2A on Ser137, the latter being inhibited by 5-ITu. It has also been reported that the macro domain of Histone macroH2A controls the levels of Ser10 and Thr3 phosphorylation of histone H3 in human cells and would be involved in controlling chromatin condensation [21,22]. The functionality of Haspin in these mechanisms remains to be confirmed.…”
Section: Haspin Substratesmentioning
confidence: 98%